Τηλεοπτικές διαφημίσεις και γλωσσική ποικιλότητα: Προτάσεις κριτικής γλωσσικής διδασκαλίας - Fterniati, Anna; Tsami, Vasia; Archakis, Argiris (Preschool and Primary Education, 2016)
Recent studies indicate that language teaching can utilize humorous mass culture texts (e.g. TV shows, advertisements, comics, magazine articles, songs, websites), so as to enable students to detect subtle social meanings and implicit cultural values (see, among others, Archakis et al., 2014; Μοrrell, 2002; Μοrrell, & Duncan-Andrade, 2005; Stamou, 2012; Tsami et al., 2014). This study aims to propose teaching activities involving critical interpretation of humorous TV advertisements in class. The activities are designed for pupils attending the 5th and 6th grade of Greek primary school (11-12 years old). The aim of these activities is to raise the pupils’ critical language awareness by revealing hidden and normalized language ideologies inherent in the representation of geographical varieties in such texts. Thus, our teaching proposal is intended to help students realize the linguistic inequalities reproduced in such texts, thus denaturalizing linguistic homogeneity (see, among others, Blackledge, 2005). Enhancing the students’ critical language awareness is among the main goals of the multiliteracies model (Cope & Kalantzis, 2000; Κalantzis & Cope, 1999; Kalantzis et al., 2005; New London Group, 1999). This model aims to nurture the students’ communicative competence through the analysis of diverse genres in four stages: 1. Situated practice, utilizing texts provided by students, reflecting their sociocultural experiences; 2. Overt instruction, which helps students realize the linguistic and textual mechanisms used for the production and interpretation of texts; 3. Critical framing, referring to the critical interpretation of a text, based on the sociocultural context of its production; 4. Transformed practice that is reframing discourse and transferring meaning from one context to another, while producing a text. Following the multiliteracies model, this paper presents specific teaching activities to enable pupils achieve a critical interpretation of TV advertisements. Our proposal aims at helping students: Identify geographical variation and dialectophones; Become aware of dominant ideologies regarding geographical varieties, their mixing, and their speakers; Stop associating dialectophones with specific social characteristics (e.g. profession, age, education, place of origin, ability to use language variations/ languages considered as “overt prestige” etc.); Identify how non-standard varieties are denigrated and stigmatized in mass culture texts (e.g. through humor); Become aware of hidden and naturalized ideologies expressed through the humorous representations of geographical variation on TV advertisements; Realize the reasons for which geographical varieties are represented as humorous in mass culture texts. The above activities constitute part of a teaching material implemented in two public elementary schools in the prefecture of Achaia, Greece. According to the initial results, the pupils’ performance is enhanced both in terms of identifying geographical variation and humorous phrases and of interpreting the reasons for which geographical varieties are represented as humorous in mass culture texts.